Comparative study on clinical efficacy of different methods for the treatment of intramural aortic hematoma - Junfu Luo (Nature Portfolio, 2021)
Abstract To explore the difference of curative effect between different treatment modalities, in order to provide reference for the treatment of aortic intramural hematoma (IMH). 168 patients with aortic intramural hematoma diagnosed and treated from January 2010 to July 2020 were selected in the Second Affiliated Hospital of Nanchang University. Among them, 48 patients were diagnosed with Stanford A aortic intramural hematoma and 120 were diagnosed with Stanford B aortic intramural hematoma. According to the therapeutic methods, patients were divided into conservative treatment group and endovascular treatment group (TEVAR). For endovascular treatment group, according to the different timing of surgery, can be divided into acute phase group (onset within 72 h) and non-acute phase group (time of onset > 72 h).The clinical data and follow-up data were collected and analyzed by variance analysis and χ2 test. There were 168 patients diagnosed with aortic intramural hematoma 39 of them were (81.25%) Stanford A aortic intramural hematoma patients with pleural or pericardial effusion. For patient with Stanford A aortic intramural hematoma, endovascular treatment was performed in 15 patients (31.2%), and 33 cases (68.8%) for conservative treatment. The average follow-up (24.9 ± 13.9) was months. There were 120 patients with Stanford type B aortic intramural hematoma (71.4%), 60 patients received endovascular treatment (50%), and 60 patients (50%) received conservative treatment, with an average follow-up of (27.8 ± 14.6) months. For Stanford A type aortic intramural hematoma patients when the maximum aortic diameter ≥ 50 mm or hematoma thickness ≥ 11 mm, with high morbidity and mortality, positive endovascular treatment can reduce complications and death. For patients with Stanford type B aortic intramural hematoma, when the maximum aortic diameter ≥ 40 mm or hematoma thickness ≥ 10 mm, with high morbidity and mortality, positive endovascular treatment can reduce complications and death. Both Stanford type A and B aortic intramural hematoma patients could benefit from the endovascular treatment when the initial maximum aortic diameter is ≥ 50 mm or the hematoma thickness is ≥ 11 mm.